Difference between revisions of "2013 AIME II Problems/Problem 13"
(→Solution 5 (Barycentric Coordinates)) |
(→Solution 2) |
||
(37 intermediate revisions by 15 users not shown) | |||
Line 1: | Line 1: | ||
==Problem 13== | ==Problem 13== | ||
In <math>\triangle ABC</math>, <math>AC = BC</math>, and point <math>D</math> is on <math>\overline{BC}</math> so that <math>CD = 3\cdot BD</math>. Let <math>E</math> be the midpoint of <math>\overline{AD}</math>. Given that <math>CE = \sqrt{7}</math> and <math>BE = 3</math>, the area of <math>\triangle ABC</math> can be expressed in the form <math>m\sqrt{n}</math>, where <math>m</math> and <math>n</math> are positive integers and <math>n</math> is not divisible by the square of any prime. Find <math>m+n</math>. | In <math>\triangle ABC</math>, <math>AC = BC</math>, and point <math>D</math> is on <math>\overline{BC}</math> so that <math>CD = 3\cdot BD</math>. Let <math>E</math> be the midpoint of <math>\overline{AD}</math>. Given that <math>CE = \sqrt{7}</math> and <math>BE = 3</math>, the area of <math>\triangle ABC</math> can be expressed in the form <math>m\sqrt{n}</math>, where <math>m</math> and <math>n</math> are positive integers and <math>n</math> is not divisible by the square of any prime. Find <math>m+n</math>. | ||
− | |||
− | === Solution 1 === | + | ==Video Solution by Punxsutawney Phil== |
+ | https://www.youtube.com/watch?v=IXPT0vHgt_c | ||
+ | |||
+ | ==Solution 1== | ||
+ | We can set <math>AE=ED=m</math>. Set <math>BD=k</math>, therefore <math>CD=3k, AC=4k</math>. Thereafter, by Stewart's Theorem on <math>\triangle ACD</math> and cevian <math>CE</math>, we get <math>2m^2+14=25k^2</math>. Also apply Stewart's Theorem on <math>\triangle CEB</math> with cevian <math>DE</math>. After simplification, <math>2m^2=17-6k^2</math>. Therefore, <math>k=1, m=\frac{\sqrt{22}}{2}</math>. Finally, note that (using [] for area) <math>[CED]=[CAE]=3[EDB]=3[AEB]=\frac{3}{8}[ABC]</math>, because of base-ratios. Using Heron's Formula on <math>\triangle EDB</math>, as it is simplest, we see that <math>[ABC]=3\sqrt{7}</math>, so your answer is <math>10</math>. | ||
+ | |||
+ | == Solution 2 == | ||
After drawing the figure, we suppose <math>BD=a</math>, so that <math>CD=3a</math>, <math>AC=4a</math>, and <math>AE=ED=b</math>. | After drawing the figure, we suppose <math>BD=a</math>, so that <math>CD=3a</math>, <math>AC=4a</math>, and <math>AE=ED=b</math>. | ||
− | Using | + | Using Law of Cosines for <math>\triangle CED</math> and <math>\triangle AEC</math>,we get |
− | <cmath>b^2+7- | + | <cmath>b^2+7-2b\sqrt{7}\cdot \cos(\angle CED)=9a^2\qquad (1)</cmath> |
− | <cmath>b^2+7+ | + | <cmath>b^2+7+2b\sqrt{7}\cdot \cos(\angle CED)=16a^2\qquad (2)</cmath> |
So, <math>(1)+(2)</math>, we get<cmath>2b^2+14=25a^2. \qquad (3)</cmath> | So, <math>(1)+(2)</math>, we get<cmath>2b^2+14=25a^2. \qquad (3)</cmath> | ||
− | Using | + | Using Law of Cosines in <math>\triangle ACD</math>, we get |
− | <cmath> | + | <cmath>4b^2+9a^2-2\cdot 2b\cdot 3a\cdot \cos(\angle ADC)=16a^2</cmath> |
− | So, <cmath>\cos(\angle ADC)=\frac{ | + | So, <cmath>\cos(\angle ADC)=\frac{4b^2-7a^2}{12ab}.\qquad (4)</cmath> |
− | Using | + | Using Law of Cosines in <math>\triangle EDC</math> and <math>\triangle EDB</math>, we get |
<cmath>b^2+9a^2-2\cdot 3a\cdot b\cdot \cos(\angle ADC)=7\qquad (5)</cmath> | <cmath>b^2+9a^2-2\cdot 3a\cdot b\cdot \cos(\angle ADC)=7\qquad (5)</cmath> | ||
Line 29: | Line 34: | ||
Using <math>(3)</math> and <math>(7)</math>, we can solve <math>a=1</math> and <math>b=\frac{\sqrt{22}}{2}</math>. | Using <math>(3)</math> and <math>(7)</math>, we can solve <math>a=1</math> and <math>b=\frac{\sqrt{22}}{2}</math>. | ||
− | Finally, we use | + | Finally, we use Law of Cosines for <math>\triangle ADB</math>, |
− | <cmath>4(\frac{\sqrt{22}}{2})^2+1+2\ | + | <cmath>4(\frac{\sqrt{22}}{2})^2+1+2\cdot2(\frac{\sqrt{22}}{2})\cdot \cos(ADC)=AB^2</cmath> |
then <math>AB=2\sqrt{7}</math>, so the height of this <math>\triangle ABC</math> is <math>\sqrt{4^2-(\sqrt{7})^2}=3</math>. | then <math>AB=2\sqrt{7}</math>, so the height of this <math>\triangle ABC</math> is <math>\sqrt{4^2-(\sqrt{7})^2}=3</math>. | ||
Line 37: | Line 42: | ||
Then the area of <math>\triangle ABC</math> is <math>3\sqrt{7}</math>, so the answer is <math>\boxed{010}</math>. | Then the area of <math>\triangle ABC</math> is <math>3\sqrt{7}</math>, so the answer is <math>\boxed{010}</math>. | ||
− | + | == Solution 3 == | |
Let <math>X</math> be the foot of the altitude from <math>C</math> with other points labelled as shown below. | Let <math>X</math> be the foot of the altitude from <math>C</math> with other points labelled as shown below. | ||
<asy> | <asy> | ||
Line 57: | Line 62: | ||
Solving this system of equations yields <math>b=2\sqrt{7}</math> and <math>h=3</math>. Therefore, the area of the triangle is <math>3\sqrt{7}</math>, giving us an answer of <math>\boxed{010}</math>. | Solving this system of equations yields <math>b=2\sqrt{7}</math> and <math>h=3</math>. Therefore, the area of the triangle is <math>3\sqrt{7}</math>, giving us an answer of <math>\boxed{010}</math>. | ||
− | + | == Solution 4 == | |
− | Let the coordinates of A, B and C be (-a, 0), (a, 0) and (0, h) respectively. | + | Let the coordinates of <math>A</math>, <math>B</math> and <math>C</math> be <math>(-a, 0)</math>, <math>(a, 0)</math> and <math>(0, h)</math> respectively. |
− | Then <math>D = (\frac{3a}{4}, \frac{h}{4})</math> and <math>E = (-\frac{a}{8},\frac{h}{8}).</math> | + | Then <math>D = \Big(\frac{3a}{4}, \frac{h}{4}\Big)</math> and <math>E = \Big(-\frac{a}{8},\frac{h}{8}\Big).</math> |
<math>EC^2 = 7</math> implies <math>a^2 + 49h^2 = 448</math>; <math>EB^2 = 9</math> implies <math>81a^2 + h^2 = 576.</math> | <math>EC^2 = 7</math> implies <math>a^2 + 49h^2 = 448</math>; <math>EB^2 = 9</math> implies <math>81a^2 + h^2 = 576.</math> | ||
Solve this system of equations simultaneously, <math>a=\sqrt{7}</math> and <math>h=3</math>. | Solve this system of equations simultaneously, <math>a=\sqrt{7}</math> and <math>h=3</math>. | ||
− | Area of the triangle is | + | Area of the triangle is <math>ah = 3\sqrt{7}</math>, giving us an answer of <math>\boxed{010}</math>. |
− | + | ==Solution 5== | |
<asy> | <asy> | ||
size(200); | size(200); | ||
Line 74: | Line 79: | ||
label("$E$",EE,NW); | label("$E$",EE,NW); | ||
</asy> | </asy> | ||
− | |||
Let <math>BD = x</math>. Then <math>CD = 3x</math> and <math>AC = 4x</math>. Also, let <math>AE = ED = l</math>. Using Stewart's Theorem on <math>\bigtriangleup CEB</math> gives us the equation <math>(x)(3x)(4x) + (4x)(l^2) = 27x + 7x</math> or, after simplifying, <math>4l^2 = 34 - 12x^2</math>. We use Stewart's again on <math>\bigtriangleup CAD</math>: <math>(l)(l)(2l) + 7(2l) = (16x^2)(l) + (9x^2)(l)</math>, which becomes <math>2l^2 = 25x^2 - 14</math>. Substituting <math>2l^2 = 17 - 6x^2</math>, we see that <math>31x^2 = 31</math>, or <math>x = 1</math>. Then <math>l^2 = \frac{11}{2}</math>. | Let <math>BD = x</math>. Then <math>CD = 3x</math> and <math>AC = 4x</math>. Also, let <math>AE = ED = l</math>. Using Stewart's Theorem on <math>\bigtriangleup CEB</math> gives us the equation <math>(x)(3x)(4x) + (4x)(l^2) = 27x + 7x</math> or, after simplifying, <math>4l^2 = 34 - 12x^2</math>. We use Stewart's again on <math>\bigtriangleup CAD</math>: <math>(l)(l)(2l) + 7(2l) = (16x^2)(l) + (9x^2)(l)</math>, which becomes <math>2l^2 = 25x^2 - 14</math>. Substituting <math>2l^2 = 17 - 6x^2</math>, we see that <math>31x^2 = 31</math>, or <math>x = 1</math>. Then <math>l^2 = \frac{11}{2}</math>. | ||
Line 82: | Line 86: | ||
<math>[ABC] = \frac{1}{2} AC \cdot BC \sin C = (\frac{1}{2})(4)(4)(\frac{3\sqrt{7}}{8}) = 3\sqrt{7}</math>, and our answer is <math>3 + 7 = \boxed{010}</math>. | <math>[ABC] = \frac{1}{2} AC \cdot BC \sin C = (\frac{1}{2})(4)(4)(\frac{3\sqrt{7}}{8}) = 3\sqrt{7}</math>, and our answer is <math>3 + 7 = \boxed{010}</math>. | ||
− | ===Solution | + | Note to writter: Couldn't we just use Heron's formula for <math>[CEB]</math> after <math>x</math> is solved then noticing that <math>[ABC] = 2 \times [CEB]</math>? |
+ | |||
+ | ==Solution 6 (Barycentric Coordinates)== | ||
Let ABC be the reference triangle, with <math>A=(1,0,0)</math>, <math>B=(0,1,0)</math>, and <math>C=(0,0,1)</math>. We can easily calculate <math>D=(0,\frac{3}{4},\frac{1}{4})</math> and subsequently <math>E=(\frac{1}{2},\frac{3}{8},\frac{1}{8})</math>. Using distance formula on <math>\overline{EC}=(\frac{1}{2},\frac{3}{8},-\frac{7}{8})</math> and <math>\overline{EB}=(\frac{1}{2},-\frac{5}{8},\frac{1}{8})</math> gives | Let ABC be the reference triangle, with <math>A=(1,0,0)</math>, <math>B=(0,1,0)</math>, and <math>C=(0,0,1)</math>. We can easily calculate <math>D=(0,\frac{3}{4},\frac{1}{4})</math> and subsequently <math>E=(\frac{1}{2},\frac{3}{8},\frac{1}{8})</math>. Using distance formula on <math>\overline{EC}=(\frac{1}{2},\frac{3}{8},-\frac{7}{8})</math> and <math>\overline{EB}=(\frac{1}{2},-\frac{5}{8},\frac{1}{8})</math> gives | ||
Line 134: | Line 140: | ||
Then plugging gives <math>b=4</math> and <math>c=2\sqrt{7}</math>. Then the height from <math>C</math> is <math>3</math>, and the area is <math>3\sqrt{7}</math> and our answer is <math>\boxed{010}</math>. | Then plugging gives <math>b=4</math> and <math>c=2\sqrt{7}</math>. Then the height from <math>C</math> is <math>3</math>, and the area is <math>3\sqrt{7}</math> and our answer is <math>\boxed{010}</math>. | ||
+ | |||
+ | ==Solution 7== | ||
+ | Let <math>C=(0,0), A=(x,y),</math> and <math>B=(-x,y)</math>. | ||
+ | It is trivial to show that <math>D=\left(-\frac{3}{4}x,\frac{3}{4}y\right)</math> and <math>E=\left(\frac{1}{8}x,\frac{7}{8}y\right)</math>. Thus, since <math>BE=3</math> and <math>CE=\sqrt{7}</math>, we get that | ||
+ | |||
+ | <cmath> | ||
+ | \begin{align*} | ||
+ | \left(\frac{1}{8}x\right)^2+\left(\frac{7}{8}y\right)^2&=7 \\ | ||
+ | \left(\frac{9}{8}x\right)^2+\left(\frac{1}{8}y\right)^2&=9 \\ | ||
+ | \end{align*} | ||
+ | </cmath> | ||
+ | |||
+ | Multiplying both equations by <math>64</math>, we get that | ||
+ | |||
+ | <cmath> | ||
+ | \begin{align*} | ||
+ | x^2+49y^2&=448 \\ | ||
+ | 81x^2+y^2&=576 \\ | ||
+ | \end{align*} | ||
+ | </cmath> | ||
+ | |||
+ | Solving these equations, we get that <math>x=\sqrt{7}</math> and <math>y=3</math>. | ||
+ | |||
+ | Thus, the area of <math>\triangle ABC</math> is <math>xy=3\sqrt{7}</math>, so our answer is <math>\boxed{010}</math>. | ||
+ | |||
+ | ==Solution 8== | ||
+ | [[File:2013 AIME II 13.png|450px|right]] | ||
+ | The main in solution is to prove that <math>\angle BEC = 90^\circ</math>. | ||
+ | |||
+ | Let <math>M</math> be midpoint <math>AB.</math> Let <math>F</math> be cross point of <math>AC</math> and <math>BE.</math> | ||
+ | |||
+ | We use the formula for crossing segments in <math>\triangle ABC</math> and get: | ||
+ | <cmath>\frac {CF}{AF}= \frac {DE}{AE} \cdot (\frac {CD}{BD} + 1) = 1 \cdot (3 + 1) = 4.</cmath> | ||
+ | <cmath>\frac {FE }{BE}= \frac {CD}{BD} : (\frac {CF}{AF} + 1) = \frac {3}{5} \implies FE = \frac {9}{5}.</cmath> | ||
+ | |||
+ | <cmath>\triangle BCF:\hspace{5mm} BC = x, CF = \frac {4}{5}x, EF = \frac {9}{5}, BF = 3, CE = \sqrt{7}.</cmath> | ||
+ | By Stewart's Theorem on <math>\triangle BCF</math> and cevian <math>CE</math>, we get after simplification | ||
+ | <cmath>x = 4 \implies BC^2 = CE^2 + BE^2 \implies \angle BEC = 90^\circ.</cmath> | ||
+ | <cmath>AE = ED, AM = MB \implies EM ||BC.</cmath> | ||
+ | <math>\angle BEC = \angle CMB = 90^\circ \implies</math> trapezium <math>BCEM</math> is cyclic <math>\implies</math> | ||
+ | <cmath>BM = CE, CM = BE \implies [ABC] = CM \cdot BM = 3 \sqrt {7} \implies 3+ 7 = \boxed{\textbf{010}}.</cmath> | ||
+ | '''vladimir.shelomovskii@gmail.com, vvsss''' | ||
+ | |||
+ | ==Solution 9== | ||
+ | Let <math>AB = 2x</math> and let <math>y = BD.</math> Then <math>CD = 3y</math> and <math>AC = 4y.</math> | ||
+ | |||
+ | <asy> | ||
+ | unitsize(1.5 cm); | ||
+ | |||
+ | pair A, B, C, D, E; | ||
+ | |||
+ | A = (-sqrt(7),0); | ||
+ | B = (sqrt(7),0); | ||
+ | C = (0,3); | ||
+ | D = interp(B,C,1/4); | ||
+ | E = (A + D)/2; | ||
+ | |||
+ | draw(A--B--C--cycle); | ||
+ | draw(A--D); | ||
+ | draw(B--E--C); | ||
+ | |||
+ | label("$A$", A, SW); | ||
+ | label("$B$", B, SE); | ||
+ | label("$C$", C, N); | ||
+ | label("$D$", D, NE); | ||
+ | label("$E$", E, NW); | ||
+ | |||
+ | label("$2x$", (A + B)/2, S); | ||
+ | label("$y$", (B + D)/2, NE); | ||
+ | label("$3y$", (C + D)/2, NE); | ||
+ | label("$4y$", (A + C)/2, NW); | ||
+ | label("$3$", (B + E)/2, N); | ||
+ | label("$\sqrt{7}$", (C + E)/2, W); | ||
+ | </asy> | ||
+ | |||
+ | By the Law of Cosines on triangle <math>ABC,</math> | ||
+ | <cmath>\cos C = \frac{16y^2 + 16y^2 - 4x^2}{2 \cdot 4y \cdot 4y} = \frac{32y^2 - 4x^2}{32y^2} = \frac{8y^2 - x^2}{8y^2}.</cmath>Then by the Law of Cosines on triangle <math>ACD,</math> | ||
+ | \begin{align*} | ||
+ | AD^2 &= 16y^2 + 9y^2 - 2 \cdot 4y \cdot 3y \cdot \cos C \\ | ||
+ | &= 25y^2 - 24y^2 \cdot \frac{8y^2 - x^2}{8y^2} \\ | ||
+ | &= 3x^2 + y^2. | ||
+ | \end{align*}Applying Stewart's Theorem to median <math>\overline{BE}</math> in triangle <math>ABD,</math> we get | ||
+ | <cmath>BE^2 + AE \cdot DE = \frac{AB^2 + BD^2}{2}.</cmath>Thus, | ||
+ | <cmath>9 + \frac{3x^2 + y^2}{4} = \frac{4x^2 + y^2}{2}.</cmath>This simplifies to <math>5x^2 + y^2 = 36.</math> | ||
+ | |||
+ | Applying Stewart's Theorem to median <math>\overline{CE}</math> in triangle <math>ACD,</math> we get | ||
+ | <cmath>CE^2 + AE \cdot DE = \frac{AC^2 + CD^2}{2}.</cmath>Thus, | ||
+ | <cmath>7 + \frac{3x^2 + y^2}{4} = \frac{16y^2 + 9y^2}{2}.</cmath>This simplifies to <math>3x^2 + 28 = 49y^2.</math> | ||
+ | |||
+ | Solving the system <math>5x^2 + y^2 = 36</math> and <math>3x^2 + 28 = 49y^2,</math> we find <math>x^2 = 7</math> and <math>y^2 = 1,</math> so <math>x = \sqrt{7}</math> and <math>y = 1.</math> | ||
+ | |||
+ | Plugging this back in for our equation for <math>\cos C</math> gives us <math>\frac{1}{8}</math>, so <math>\sin C = \frac{3\sqrt{7}}{8}.</math> We can apply the alternative area of a triangle formula, where <math>AC \cdot BC \cdot \sin C \cdot \frac{1}{2} = 3\sqrt{7}.</math> Therefore, our answer is <math>\boxed{010}</math>. | ||
+ | |||
+ | |||
+ | ==Video Solution== | ||
+ | |||
+ | https://youtu.be/jVV4pYDGxGE?si=fDGGUOvCZRfdwUEz | ||
+ | |||
+ | ~MathProblemSolvingSkills.com | ||
+ | |||
==See Also== | ==See Also== | ||
{{AIME box|year=2013|n=II|num-b=12|num-a=14}} | {{AIME box|year=2013|n=II|num-b=12|num-a=14}} | ||
+ | |||
+ | [[Category:Intermediate Geometry Problems]] | ||
{{MAA Notice}} | {{MAA Notice}} |
Latest revision as of 18:20, 11 August 2024
Contents
Problem 13
In ,
, and point
is on
so that
. Let
be the midpoint of
. Given that
and
, the area of
can be expressed in the form
, where
and
are positive integers and
is not divisible by the square of any prime. Find
.
Video Solution by Punxsutawney Phil
https://www.youtube.com/watch?v=IXPT0vHgt_c
Solution 1
We can set . Set
, therefore
. Thereafter, by Stewart's Theorem on
and cevian
, we get
. Also apply Stewart's Theorem on
with cevian
. After simplification,
. Therefore,
. Finally, note that (using [] for area)
, because of base-ratios. Using Heron's Formula on
, as it is simplest, we see that
, so your answer is
.
Solution 2
After drawing the figure, we suppose , so that
,
, and
.
Using Law of Cosines for and
,we get
So,
, we get
Using Law of Cosines in , we get
So,
Using Law of Cosines in and
, we get
, and according to
, we can get
Using and
, we can solve
and
.
Finally, we use Law of Cosines for ,
then , so the height of this
is
.
Then the area of is
, so the answer is
.
Solution 3
Let be the foot of the altitude from
with other points labelled as shown below.
Now we proceed using mass points. To balance along the segment
, we assign
a mass of
and
a mass of
. Therefore,
has a mass of
. As
is the midpoint of
, we must assign
a mass of
as well. This gives
a mass of
and
a mass of
.
Now let be the base of the triangle, and let
be the height. Then as
, and as
, we know that
Also, as
, we know that
. Therefore, by the Pythagorean Theorem on
, we know that
Also, as , we know that
. Furthermore, as
, and as
, we know that
and
, so
. Therefore, by the Pythagorean Theorem on
, we get
Solving this system of equations yields
and
. Therefore, the area of the triangle is
, giving us an answer of
.
Solution 4
Let the coordinates of ,
and
be
,
and
respectively.
Then
and
implies
;
implies
Solve this system of equations simultaneously,
and
.
Area of the triangle is
, giving us an answer of
.
Solution 5
Let . Then
and
. Also, let
. Using Stewart's Theorem on
gives us the equation
or, after simplifying,
. We use Stewart's again on
:
, which becomes
. Substituting
, we see that
, or
. Then
.
We now use Law of Cosines on .
. Plugging in for
and
,
, so
. Using the Pythagorean trig identity
,
, so
.
, and our answer is
.
Note to writter: Couldn't we just use Heron's formula for after
is solved then noticing that
?
Solution 6 (Barycentric Coordinates)
Let ABC be the reference triangle, with ,
, and
. We can easily calculate
and subsequently
. Using distance formula on
and
gives
But we know that , so we can substitute and now we have two equations and two variables. So we can clear the denominators and prepare to cancel a variable:
Then we add the equations to get
Then plugging gives and
. Then the height from
is
, and the area is
and our answer is
.
Solution 7
Let and
.
It is trivial to show that
and
. Thus, since
and
, we get that
Multiplying both equations by , we get that
Solving these equations, we get that and
.
Thus, the area of is
, so our answer is
.
Solution 8
The main in solution is to prove that .
Let be midpoint
Let
be cross point of
and
We use the formula for crossing segments in and get:
By Stewart's Theorem on
and cevian
, we get after simplification
trapezium
is cyclic
vladimir.shelomovskii@gmail.com, vvsss
Solution 9
Let and let
Then
and
By the Law of Cosines on triangle
Then by the Law of Cosines on triangle
\begin{align*}
AD^2 &= 16y^2 + 9y^2 - 2 \cdot 4y \cdot 3y \cdot \cos C \\
&= 25y^2 - 24y^2 \cdot \frac{8y^2 - x^2}{8y^2} \\
&= 3x^2 + y^2.
\end{align*}Applying Stewart's Theorem to median
in triangle
we get
Thus,
This simplifies to
Applying Stewart's Theorem to median in triangle
we get
Thus,
This simplifies to
Solving the system and
we find
and
so
and
Plugging this back in for our equation for gives us
, so
We can apply the alternative area of a triangle formula, where
Therefore, our answer is
.
Video Solution
https://youtu.be/jVV4pYDGxGE?si=fDGGUOvCZRfdwUEz
~MathProblemSolvingSkills.com
See Also
2013 AIME II (Problems • Answer Key • Resources) | ||
Preceded by Problem 12 |
Followed by Problem 14 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.